Respuesta :

Answer:

x = 0

Step-by-step explanation:

-2(2 − 2x) = 4 − 8(1 − x)

Apply the distributive property:

−2(2 − 2x) = 4 − 8(1 − x)

(−2)(2) + (−2)(−2x) = 4 + (−8)(1) + (−8)(−x)

−4 + 4x = 4 + (−8) + 8x

Combine like terms:

4x − 4 = (8x) + (4+−8)

4x − 4 = 8x + (−4)

4x − 4 = 8x − 4

Subtract 8x from both sides:

4x − 4 − 8x = 8x − 4 − 8x

−4x − 4 = −4

Add 4 to both sides:

−4x − 4 + 4= −4 + 4

−4x = 0

Divide both sides by -4:

-4x/-4 = 0/-4

x = 0

Answer: 0

Step-by-step explanation:

ACCESS MORE